PENGARUH LABA DAN ARUS KAS TERHADAP FINANCIAL DISTRES S - Sri Islami Rahayu; Acep Suherman; Andri Indrawan (Universitas Prof.Hazairin,SH Bengkulu, 2021)
This study aims to examine the effect of profit and cash flow on Financial distress. The vaiabels used in this study are profit, cash flow, and Financial distress. This research was conducted using quantitative methods with an associative approach. The population in this study is the annual manufacturing company financial statements listed on the Indonesia Stock Exchange (IDX) for the 2017-2020 period asmany as 30 company’s. The sampling technique uses nonprobability sampling method with purposive sampling technique. The analysis technique used in this study is the descriptive statistics, normality test, multicollinearity test, heteroscedasticity test, autocorrelation test, multiple linear regression analysis, t test, F test, and the coefficient of determination test. With the results of profit has an effect on financial distress with a significance of 0,006 < 0,05 and tcount > ttabel (2,928 > 2,034), cash flow does not effect financial distress with a significance of 0,053 > 0,05 and tcount < ttabel (-2,066 < 2,034) and profit and cash flow simultaneously effect financial distress with a significance of 0,005 < 0,05 and Fcount 6,173 > Ftabel 3,29.